Application of the React Navigation Library for Creating Complex Routes in Mobile Applications (International Journal of Engineering and Computer Science, 2025)
This article examines the use of the React Navigation library for structuring navigation in mobile applications developed on the React Native platform. Modern mobile technologies demand advanced solutions for implementing navigation mechanisms, which necessitates the use of flexible tools. The React Navigation library provides developers with the ability to build multi-level routes and manage navigation states through dynamic transitions between screens. Given the importance of navigation quality in contemporary mobile applications, this aspect significantly influences user perception and attitudes toward the product. The methodology includes an analysis of documentation, existing solutions, and practical work with the React Navigation library, demonstrated through real-world mobile application examples. Various types of navigation—stack, tab-based, as well as custom implementations for unique interfaces—are explored. The primary focus is on optimizing performance when utilizing complex routes, animations, asynchronous operations, and transitions between screens tailored for specific solutions. The results demonstrate that React Navigation provides developers with robust tools for creating flexible routes while ensuring a consistent user experience. The library's modular system allows for easy adaptation of navigation to any specific project, whether it is a simple application or a multitasking system with multiple screens and interactions. This article will be of interest to those working on mobile applications, including developers, UI engineers, and specialists in functional solutions for mobile platforms.